Cadeia de suprimentos e gerenciamento de estoques: um olhar para as empresas vitivinícolas de Santana do Livramento - RS - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The municipality of Santana do Livramento is home to large companies that produce grapes for the manufacture of wines and sparkling wines, due to the geographical location of the municipality, far from large distribution centers. stocks, areas responsible for determining the success or failure of an economic activity. In order to carry out the present work, a case study was carried out with the winegrowers who have grape cultivation and wine production in their factory plants. Data collection was done through semi-structured interviews with open questions, leaving interviewees free to complement what they considered important. Soon after the data collection, these were interpreted and the results were determined. The conclusions point out that the raw material used is quite distant from the municipality, with the result that the companies participating in the study suffer a series of difficulties to manage the supply chain and have high costs of stocking their raw material.
Supply chain and stock management: a look at the wine building companies in Santana do Livramento
Keywords: Vinícolas; Gerenciamento; Cadeia de suprimentos; Estoques; Wineries; Management; Supply chain; Stocks; CNPQ::CIENCIAS SOCIAIS APLICADAS